MASSAGE EFFECT ON PSYCHOEMOTIONAL STATE AND BLOOD GLUCOSE IN TYPE 1 DIABETES ADOLESCENTS - Veseta, Una; Pakalnišķe, Māra; Trups-Kalne, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In 2021, there were approximately 1.5 million people under age 20 with type 1 diabetes mellitus (T1D) worldwide. Massage affects both physiological processes and also improves the psycho-emotional state. There have been studies on diabetes and the effects of massage on blood glucose levels, but the topic is under-researched. The purpose of the study: to find out the effect of classical massage on the psycho-emotional state and blood glucose level (BGL) in adolescents with T1D. Fifteen adolescents aged 12 to 16, diagnosed with T1D for at least six months, participated in the study. During the study, teenagers were given five classic back massages (once a week, 30 minutes). BGL was measured with glucometer before and after each massage. Participants completed the Positive and Negative Affect Schedule before each massage and the Depression Anxiety Stress Scales at the beginning and end of all massage sessions. Oscillometric method was used to determine the heart rate. The study results show that classical massage positively affects BGL and emotional states in adolescents with T1D. The overall results show a reduced BGL as well as heart rate. Although the differences are not statistically significant, and the effect is not large due to the sample size, the change direction is clinically relevant. When evaluating the results, it is necessary to consider the adolescents' specific age.